Comparison of children with and without dyslexia using functional head impulse test and pediatric balance scale - Ölçek, Gül; Çelik, İlayda; Başoǧlu, Yuşa; Kaymakçı, Sude; Gürlek, Emre (Frontiers in Neurology, 2023)
Purpose The aim of this study is to compare functionality of vestibulo-ocular reflex (VOR) responses to evaluate the functional properties of the vestibular system and daily balance performance in children with dyslexia and children with normal development. Method Fifteen participants diagnosed with dyslexia were included in the study group (SG), and 15 healthy participants were included in the control group (CG). All groups underwent Functional Head Impulse Test (f-HIT) and Pediatric Balance Scale (PBS). f-HIT was performed with at least 15 head impulses at 4000-5000-6000°/s2 randomly to the right and left in the plane of the horizontal semicircular canal (SCC). Statistical analysis was performed using descriptive statistics and the Mann-Whitney U test. Results SG percentage values were obtained lower than CG percentage values. Comparisons between the two groups showed that there was a significant difference in all parameters (4000-5000-6000°/s2 and total) in the right-side stimulation, there was significant difference for 4,000 s2 and total correct answers in the left side. In addition, although there was no significant difference between the groups in terms of the PBS score, the SG scores were lower (p = 0.062). Conclusions As a novel test, f-HIT, revealed the difference in functionality of vestibular performance in the dyslexia group. In the dyslexia group, f-HIT may be helpful in evaluating and monitoring the vestibular system.